INTERVENING: THE GURINDAM XII VALUE OF THE TWELVE INTO THE MEANING OF LIFE CONCEPT - Izul Haidi Afdilah; M Yunus Sudirman; Nanda Alfan Kurniawan; Randi Saputra; Suci Nora Julina Putri; Karisma Khoirul Hidayah; Rona Rohmah Dini (Jurnal Pendidikan Humaniora, 2021)
Abstract: Every culture has different rules and values that develop and are believed together, as well as Melayu people who have values that are believed and applied jointly by the people, one of them is gurindam XII. In line with this, the values contained in gurindam XII have a very broad value, especially the value of meaningfulness of life. Meaningfulness of life in question is how the Melayu people in finding and developing so that the meaningfulness of life develops optimally. The purpose of this study is to provide a grouped indicators contained in gurindam XII into the meaning of life component, as well as laying the foundation stone for further researchers to research the meaning of life of Melayu society. The method used was qualitative with Literature Study. The conclusion from the study is that the values contained in gurindam are very broad and deep, therefore a detailed analysis is needed to get the desired suitability. Alhamdulillah, this research has succeeded in formulating the essence of gurindam XII into the Meaning of Life component.Keywords: Gurindam XII, meaning of life, melayu literature Abstrak: Setiap budaya memiliki aturan dan nilai berbeda yang berkembang dan diyakini bersama, begitu juga dengan masyarakat Melayu yang memiliki nilai-nilai yang diyakini dan diterapkan bersama oleh masyarakat, salah satunya adalah gurindam XII. Sejalan dengan itu, nilai-nilai yang terkandung dalam gurindam XII memiliki nilai yang sangat luas, terutama nilai kebermaknaan hidup. Kebermaknaan hidup yang dimaksud adalah bagaimana masyarakat Melayu dalam mencari dan mengembangkan agar kebermaknaan hidup berkembang secara optimal. Tujuan penelitian ini adalah untuk memberikan pengelompokan indikator-indikator yang terkandung dalam gurindam XII ke dalam komponen makna hidup, serta meletakkan landasan bagi peneliti selanjutnya untuk meneliti makna hidup masyarakat Melayu. Metode yang digunakan adalah kualitatif dengan Studi Literatur. Kesimpulan dari penelitian ini adalah nilai-nilai yang terkandung dalam gurindam sangat luas dan dalam, oleh karena itu diperlukan analisis yang mendetail untuk mendapatkan kesesuaian yang diinginkan. Alhamdulillah penelitian ini berhasil merumuskan intisari gurindam XII ke dalam komponen Makna Hidup.Kata kunci: Gurindam XII, makna hidup, sastra melayu